Ladies, let's talk about masturbation! or maybe not. - Teo, Yin Yin. (2013)
This paper investigates the role that women themselves play in the reproduction of, and resistance, to existing gender norms that stifle the open discussion of masturbation among women. It is also important to note that while women succumb to the pressure to conform to gender/sexual norms, we should not ignore how some women may resist such a feminine ideal through various strategies. We need to focus on the role women play in the processes that shape their identities, specifically, the importance of female subjectivity and agency in the construction of their own sexualities and body (Barrett and Phillips 1992; Bartky 1990; Pringle 1995; Weedon 1987).